Fresh yeast additives improve immune parameters and reduce respiratory disease in heifers finished in feedlots - Mauricio Paulo Virmond; Patricia Santos Rossi; Anna Victoria Antunes; Rafael Igor Mattei; Natali Regina Schllemer; Gabriela Rodrigues Thomaz; Gabriela Garbossa; Mikael Neumann; Heloisa Godoi Bertagnon (Semina: Ciências Agrárias, 2020)
Although cattle feedlot presents productive advantages, this management generates stress, which may impact immunity and increase the incidence of respiratory diseases. Because the immunostimulatory potential of yeasts, this study aimed to verify whether supplementation of cattle with fresh yeast promotes an increase in innate immunity and, consequently, reduces the occurrence of respiratory diseases in heifers finished in feedlots. A total of 32 heifers, finished in feedlots, were randomly divided into two treatments and 16 repetitions: A control group (n=16; 7 g day -1 per animal of corn kernel) and a yeast group (n=16, 7 g day -1 per animal of the commercial product with fresh yeast additive). At day 0, 16 days after acclimatisation to the feedlot, and at days 28, 56 and 84, leukogram, serum haptoglobin, oxidative metabolism neutrophil, and indicators of respiratory diseases (nasal temperatures, nasal secretion score, and histopathological examination of lung) were evaluated. The yeast group had lower blood neutrophil counts (P = 0.02), higher neutrophil oxidative metabolism (P = 0.04) than the control group after 56 days of confinement. There was a lower frequency of animals from the yeast group with purulent nasal secretion on days 28 and 84 (P = 0.0001 and 0.008) and with histopathological lesion of pneumonia at slaughter day (P = 0.0001). The yeast group also presented lower nasal temperatures than the control group on days 28 and 84 (P = 0.02 and P= 0.08). Thus, fresh yeast additives attenuated the effects of the feedlot system in the heifer immune system and contributed to a reduction of respiratory diseases.